The Role of Intra-Household Interactions and Personal Social Network Dispersion in Air Travel Frequency in the UK - Giulio Mattioli; Joachim Scheiner (Findings)
This paper studies private air travel frequency among the UK population using a regression analysis. The analysis accounts for a large range of independent variables, including the respondents' partners' attributes, social network dispersion and migration background. We find that both having one's best friends and/or close family members abroad is associated with more frequent flights. Partners' friends living abroad also stimulate more frequent flights. Also, partners' education level and long-standing illness or disability are, respectively, positively and negatively associated with flight frequency. First generation migration background is associated with increased flying, while higher-order generation migration background (i.e. having parents or grandparents who were born abroad) is not.